Diode Laser Irradiation in Endodontic Therapy through Cycles - in vitro Study - Trišić Dijana; Ćetenović Bojana; Jovanović Igor; Gjorgievska Elizabeta; Popović Branka; Marković Dejan (Balkan Stomatological Society, 2017)
Background/Aim: The aim of this in vitro study was to investigate the influence of irradiation cycles and resting periods, on thermal effects on the external root surface during root canal irradiation of two diode laser systems (940 nm and 975 nm), at output powers of 1 W and 2 W in continuous mode. In previous studies the rising of temperature above 7°C has been reported as biologically accepted to avoid periodontal damage on the external root surface. Material and Methods: Twenty human inferior incisors were randomly distributed into four groups, the 940 nm, and the 975 nm diode laser irradiation, both with an output power of 1 W and 2 W, in continuous mode. The thermographic camera was used to detect temperature variations on the external root surface. Digital radiography of the samples was made. Results: After three cycles of irradiation, at apical third of the root, mean temperature variation by 940 nm diode laser irradiation was 2.88°C for output power of 1 W, and 6.52°C for output power of 2 W. The 975 nm laser caused a higher temperature increase in the apical region, with temperature variation of 13.56°C by an output power of 1 W, and 30.60°C at 2 W, with a statistical significance of p ≤ 0.0001 between two laser systems compared for the same power. The resting periods of 20 s between cycles were enough to lower temperature under 7°C in the case of 1 W and 2 W for 940 nm diode laser, while for 975 nm laser, after three irradiation cycles overheating occurred at both output power rates. Conclusion: Three cycles irradiation of 940 nm diode laser, with resting periods of 20 seconds, allowed safe usage of 1 W and 2 W in CW for endodontic treatment. For 975 nm at a power rate of 1 W, the last resting period drop the temperature near the safe limit and it came under 7°C in a period less than a minute, while at the power of 2 W the resting periods were not long enough for the safe temperature decrease.